Perturbation of climatic response at maritime glaciers? - Winkler, Stefan; Nesje, Alte (ERDKUNDE, 2009)
Detailed analyses of mass-balance and length-variation data from maritime mountain glaciers in southern Norway reveal that some frequent assumptions of the relationship between mass-balance data and terminus response need to be reconsidered. In particular, the possibility of a ‘regime shift’ in the mass-balance drivers and the virtual absence of any frontal reaction time due to a perturbation of the dynamic response of the glacier tongue occurring around c. AD 2000 are discussed. Although above-average summer air temperatures unambiguously caused the most recent retreat, it is not clearly linked to mass-balance data. Furthermore, the maritime glaciers of southern Norway are in general not entirely determined by air temperature changes. Relative contributions of the winter balance to the annual net mass balance variations were high during the last decades of the 20th century and a considerable increase in ice mass during the 1990s was caused by increased winter precipitation. Therefore, the parameter ‘annual air temperature’ cannot be applied to explain glacier length variations.